PENGARUH STRATEGI MANAJEMEN PERUBAHAN DAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MERUBAH BUDAYA ORGANISASI - Sunasih Mulianingsih (GoAcademica Research dan Publishing, 2020)
Organizational culture is one of several situational moderators that are crucial in evaluating leadership effectiveness. Furthermore, these ideas reflect all the elements that